Taking Stock of Industrial Ecology - Clift, Roland; Druckman, Angela (Springer International Publishing : Imprint: Springer, 2016)
How can we design more sustainable industrial and urban systems that reduce environmental impacts while supporting a high quality of life for everyone? What progress has been made towards reducing resource use and waste, and what are the prospects for more resilient material-efficient economies? What are the environmental and social impacts of global supply chains, and how can they be measured and improved? Such questions are at the heart of the emerging discipline of industrial ecology, covered in Taking Stock of Industrial Ecology. Leading authors, researchers and practitioners review how far industrial ecology has developed and current issues and concerns, with illustrations of what the industrial ecology paradigm has achieved in public policy, corporate strategy and industrial practice. It provides an introduction for students coming to industrial ecology and for professionals who wish to understand what industrial ecology can offer, a reference for researchers and practitioners, and a source of case studies for teachers.